TEACHER ROLES USED IN ENGLISH CLASSROOM INTERACTION - Puan Suri Mira Annisa; Bahagia Saragih; Halima Tussa Diah Bancin (Jurnal Darma Agung, 2021)
This research aims at finding out Teacher Roles and describe how teacher roles applied in English classroom interaction. A descriptive qualitative design used in this study. The data were collected by observing and recording of the three English teachers’ roles and all of their students from three classrooms at SMP Muhammadiyah 1 Medan. The data analyzed based on Harmer & Brown theory. The findings of this study showed the first teacher applied the eight teacher’s role completely in teaching and learning process. The second teacher also applied the eight roles of teacher. The third teacher didn’t apply teacher’s role maximally because she missed the role of teacher as assessor in teaching and learning process. It can be concluded that generally teaching and learning process of English subject in SMP Muhammadiyah 1 Medan was active or interesting learning. In addition, the three teachers maximally applied the teacher Roles in class.